A new species of the sanguinea-group Quatrefages, 1866 (Annelida: Eunicidae: Marphysa) from the Philippines - Glasby, Christopher J.; Mandario, Mary Anne E.; Burghardt, Ingo; Kupriyanova, Elena; Gunton, Laetitia M.; Hutchings, Pat A. (Zootaxa, 2019)
A new species of the Marphysa sanguinea group, M. iloiloensis n. sp. (Annelida: Eunicida: Eunicidae), is described from the Marine Annelids Hatchery of the Southeast Asian Fisheries Development Center, Aquaculture Department (SEAFDEC- AQD), Iloilo Province, Philippines. It represents the first record of this group in the Philippines. The new species is most similar morphologically to M. hongkongensa Wang, Zhang & Qiu, 2018, but can be distinguished from it by having fewer branchial filaments, a pair of faint eyes (absent in M. hongkongensa), and in slight differences in jaw morphology and chaetation. The embryos of the new species develop inside a jelly cocoon attached to the entrance of the adult burrow; this is the first time that egg-containing cocoons have been found in any species of the sanguinea-group. Phylogenetic analysis based on the mitochondrial gene cytochrome c oxidase subunit I (COI) revealed that Marphysa iloiloensis n. sp. is genetically distinct from all other analysed Marphysa species and forms a sister group to M. hongkongensa. A revised identification key to members of the sanguinea-group in Southeast Asia is provided.